Exploring the Grape Agrivoltaic System: Climate Modulation and Vine Benefits in the Puglia Region, Southeastern Italy - Andrea Magarelli; Andrea Mazzeo; Giuseppe Ferrara (Horticulturae)
Climate change poses significant challenges to agriculture, a sector with a long-standing tradition in the Mediterranean basin. The region faces altered rainfall patterns, extreme temperatures, aridification, loss of biodiversity, and changes in crop yield and quality. These impacts, combined with intensive farming practices, threaten long-term agricultural sustainability. This study investigates agrivoltaics (AVs), a dual-use technology that integrates solar energy production (photovoltaic panels) with agriculture, as a potential solution to enhance resilience and adaptation of crops. Research at an AV system in Puglia (Southeastern Italy), combined with grapevine (Vitis vinifera L.), assessed soil moisture, temperature, and microclimate conditions together with vine yield and fruitfulness. Results showed that shading from photovoltaic panels increased soil moisture and moderated soil temperature, thus benefiting crops. Vines beneath the panels yielded more grapes (+277%) than in the full sun, confirmed by even the better bud fruitfulness of the shaded canes. While panels had minimal impact on air temperature, they reduced wind speed and vapor pressure deficit, creating a better microenvironment for vines. Spectral analysis revealed an increase in UV and blue light under the panels, potentially affecting photosynthesis. The AV system also produced substantial electricity, more than 90% compared to a ground-mounted system, demonstrating its dual-use application. The higher land equivalent ratio (LER) achieved by the AV system (3.54) confirmed that such systems can be advantageous in areas with a Mediterranean climate, allowing crop and energy production on the same land.